CARPAL TUNNEL SYNDROME PADA PEMECAH BATU DI DESA ROWOSARI KECAMATAN TEMBALANG SEMARANG - , Siswi Jayanti, dr., Prof. Dr. dr. KRT Adi Heru Sutomo, M.Sc, D.Comm Nutr, DLSHTM, PK ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Objective: The objective of this study was to analyze the correlation between repetition (frequency of movement), force (length of hammer, the fitting of hammer to the hand, weight of hammer) and work periode and Carpal Tunnel Syndrome (CTS) among manually stone breaker at Rowosari Village, Tembalang district, Semarang City. Method: A cross sectional design was used in this study to 79 person. Independent variables were frequency of movement, length of hammer, the fitting of hammer to hand, weight of hammer and working periode). Dependent variable was CTS. All of samples were women with incidental sampling method. Data collection was done through interviews about characteristic of samples, CTS complains and work periode, inspections about working condition, sensibility test (two point discrimination and monofilament) and provocation test (Phalenâs and Tinelâs) and meassurment of frequency, length of hammer, diameter of hammer, anthropometry of hand, weight of hammer. Result: The study found that there were no significant correlation between frequency of movement (p = 0,062), length of handle (p = 0,181), the fitting of hammer to hand (p = 0,292), weight of hammer (p = 0,483) and working periode (p = 0,488)) and CTS. Contribution of all independent variables to cause CTS was 1,7 %, and 98,3 % by the other factors. Conclution: no significant correlation were found between frequency, length of handle, the fitting of handle to hand, weight of hammer, work periode and CTS. Relative contribution of all variables to cause CTS were 1,7% and 98,3% cause by the other factors.